The Strategy of Developing Sweet Potato Cultivation in Tidal Land - Prihastuti, Prihastuti (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2016)
The development of sweet potato cultivation in tidal land has begun. These activities require an appropriate invention in agricultural technology. An integrated management in physical, chemical and biological aspect also needs to be done. The content of soil microbes in tidal land is low, but it’s fairly high diversity can be used to improve the soil fertility. This paper describes some success of microbiological studies on tidal land. Further attempt is by integrate the potential of soil microbes utilization which supported by LEISA (Low External Input Sustainable Agriculture) technology.The success of this activity supports the national food security program and realizing sustainable agricultural system in the utilization of tidal land.